Enhancing KBIH Management Website System Design Study: Meningkatkan Manajemen KBIH Studi Perancangan Sistem Website - Shella, Deva Martha; Mauliana, Metatia Intan (Universitas Muhammadiyah Sidoarjo, 2024)
KBIH Jabal Nur is an institution that operates in the field of managing prospective Hajj and Umrah pilgrims in groups. KBIH Jabal Nur is an institution under the auspices of PDM Sidoarjo. KBIH Jabal Nur was founded in 2011, currently the information system is still traditional or manual where promotions for Hajj and Umrah registration are spread through verbal communication. Therefore, the author took the initiative to create a web-based information system to make it easier for users or pilgrims to find more in-depth information about Hajj and Umrah registration. The system used by the author is SDLC or system development life cycle, this method is used in creating or developing information systems that aim to solve problems effectively. On this website there is the history of KBIH, management structure, promotion of guidance registration and also social media. Of course, this website was designed using the SDLC method or system development life cycle to make it easier to create an author's website. Highlights : KBIH Jabal Nur enhances Hajj and Umrah registration process. Web-based system developed using SDLC methodology. Website offers history, management, promotion, and social media integration. Keywords : KBIH Jabal Nur, web-based information system, SDLC methodology, pilgrimage registration, Hajj and Umrah.